2001
DOI: 10.1176/appi.ps.52.7.953
|View full text |Cite
|
Sign up to set email alerts
|

Familiarity With and Social Distance From People Who Have Serious Mental Illness

Abstract: Approaches to social change that increase the public's familiarity with serious mental illness will decrease stigma. Further studies are warranted that focus on how contact between members of the general public and persons who have serious mental illness may be facilitated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

37
323
3
15

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 434 publications
(378 citation statements)
references
References 47 publications
37
323
3
15
Order By: Relevance
“…This finding suggests that the relationship between stigma and utilization may have changed as a result of treatment experiences. Such an explanation is broadly consistent with research on social distance, wherein exposure to the stigmatized context (that is, treatment) can lead to decreases in desired social distance (19). Second, the results are also consistent with research showing that levels of stigma change in association with treatment (31).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This finding suggests that the relationship between stigma and utilization may have changed as a result of treatment experiences. Such an explanation is broadly consistent with research on social distance, wherein exposure to the stigmatized context (that is, treatment) can lead to decreases in desired social distance (19). Second, the results are also consistent with research showing that levels of stigma change in association with treatment (31).…”
Section: Discussionsupporting
confidence: 81%
“…This balance permitted us to draw from existing knowledge and simultaneously incorporate constructs specific to a particular ethnic minority group. Of the four measures, three have been studied previously—Perceived Discrimination-Devaluation (PDD), Stigma Concerns About Mental Health Care (SCMHC), and Social Distance (SD) (1921)—and one—the Latino Scale for Antidepressant Stigma (LSAS)—was generated specifically for Latinos on the basis of qualitative work (18). The analyses used depression treatment utilization outcomes to examine the measures’ internal consistency reliability, convergent validity, construct validity, and criterion-related validity.…”
mentioning
confidence: 99%
“…55 Stigma and shame have been heavily implicated in poor help-seeking behaviour. 56 The fear of being labelled 'mad' or being perceived as mentally ill can lead to sufferers distancing themselves from others in their social roles and interactions. 56 Social distance is a measurement of an individual's readiness to inter-relate with a target person in a variety of relationships.…”
Section: Stigma and Shamementioning
confidence: 99%
“…56 The fear of being labelled 'mad' or being perceived as mentally ill can lead to sufferers distancing themselves from others in their social roles and interactions. 56 Social distance is a measurement of an individual's readiness to inter-relate with a target person in a variety of relationships. 57 Studies have shown that those with previous extensive communications with individuals experiencing mental health problems feel the need for less social distance than those with limited or no experience of such difficulties.…”
Section: Stigma and Shamementioning
confidence: 99%
“…Of the three levels at which stigma operates, public stigma (defined as the phenomenon whereby large social groups have negative attitudes towards and beliefs about, and even act against those with a disenfranchised trait -like mental illness (Corrigan and Watson 2002)) has received the greatest attention. Public stigma related to mental illness has been investigated in a broad range of groups including the general public Kobau et al 2009), students (Brown 2008;Chan et al 2009;Corrigan et al 2001;Faigin and Stein 2008;Mann and Himelein 2008;Penn et al 1994;Reinke et al 2004) police , and mental health workers Schulze 2007). In all groups in which public stigma has been investigated, negative beliefs about, and attitudes and behaviors towards individuals with mental illness have been identified.…”
Section: Introductionmentioning
confidence: 99%